Parental knowledge and support for decision-making regarding measles rubella immunization - Ritonga, Christina Ruth Lestari; Lamana, Aspia; Astuti, Wahyu (Borneo Scientific Publishing, 2025)
Measles remains a significant health concern in Indonesia. The government continues to promote immunization programs to achieve optimal public health and a prosperous society. According to the Regulation of the Minister of Health No. 12 of 2017, immunization aims to build immunity so that individuals who are later exposed experience only mild symptoms. This study aimed to determine the relationship between parents’ knowledge and support in decision-making regarding MR (Measles Rubella) immunization among kindergarten students in Sungai Ambawang Kuala Village. Using a quantitative descriptive-analytic design with a cross-sectional approach, data were collected at one point in time.The results showed a significant relationship between parents’ knowledge (p < 0.05; OR = 15.6) and parental support (p < 0.05; OR = 26) with the decision to administer MR immunization. In conclusion, improving parental knowledge and support is essential to increase MR immunization coverage and program success.